Financial slack and technology commercialization: contingent effects of executive international experience in declining firms - Hao Ren; Simon Kwong Choong Mun (HM Journals, 2025)
Internal resource conversion into innovation gains paramount importance due to speedy technological changes alongside intense global competition particularly since organizations experiencing performance decline must succeed. Organizational research lacks sufficient understanding about strategic implementation of financial slack during periods of downturn. Financial slack and technology commercialization in declining firms demonstrate a relationship which depends on the influence of executive international experience according to this study. As an application of resource-based view and upper echelons theory the paper defines financial slack as a strategic resource with three distinct types (available, absorbed and potential) that enables innovation when properly deployed. The research study explores how different degrees of executive international background impact the firm's process of turning slack resources into innovative results throughout sustained organizational decline. The research discovers that international leadership experience intensifies the positive R&D investments brought by slack resources which subsequently improves technological commercialization success. The findings contribute both theoretical understanding and practical application about how leader backgrounds influence resource strategies related to innovation-based renewal of underperforming firms.